HUBUNGAN BBLR DENGAN KEJADIAN SEPSIS NEONATORUM DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2015 - Putri Azzahroh; Wahyu Ekaningtyas Utami (Jurnal Ilmu dan Budaya, 2017)
Infection is one of the main causes of the high mortality rate of mothers and newborns. There are several factors that can cause infections in infants including Low Birth Weight (LBW). The aim of this study is to identify the relationship of LBW with the incidence of neonatal sepsis in the Dr. H. Abdul Moeloek hospital in Lampung in 2015. The method used in this research is analytical case-control study. This study population is 123 infants of cases group while the control group has 1363 infants. Simple Random Sampling is used to take a sample of 94 babies for cases group and 94 babies as control samples. The data are obtained by looking at medical records in the Dr. H Abdul Moeloek hospital. The data are processed using the univariate and bivariate analysis. The results showed that in the case group 63 infants (67%) of babies have low birth weight, whereas in the control group, 53 infants (56.4%) did not experience low birth weight, with (p-value = 0.002 and OR = 2.627), which means there is a relationship between the incidence of LBW with neonatal sepsis. The researcher therefore suggested to the hospital for early detection in antenatal care to prevent complications in childbirth, postpartum, taking care of newborn babies and provide counseling to maintain health in pregnancy and how to care for babies with neonatal emergencies.